KESIAPAN ALAT REACH STACKER, PENGALAMAN DAN KETERAMPILAN OPERATOR TERHADAP PRODUKTIVITAS LIFT ON/OFF - Lisa Arum Mutiara; Irma Rustini Aju; R.A. Norromadani Yuniati (Proceeding Maritime Business Management Conference, 2023)
Container depots have various services, one of wich is Lift On/Lift Off (LOLO) activities. Problems at the Surabaya container depot are related to unstable lift on/lift off productivity and not achieving the set taegets. This study aims to analyze the influence of heavy equipment readiness, experiences and skills of reach stacker operators on lift on/ lift off productivity. This study uses quantitative methods with multiple linear regression analysis techniques by distributing questionnaires. The samples used were 36 permanent employees. The results of this study show that the experience of the reach stacker operator has a significant effect on the productivity of the lift on/lift off, the more experience the operator has, the more competent he is in operating the equipment, while the readiness of the heavy equipment and the skills of the reach stacker operator do not have a significant effect on the productivity of the lift on/lift off. The calculated f value of 13.934 is greater than the f table of 2.892 so that the readiness of the heavy equipment, the experience and skills of the reach stacker operator simultaneously have a significant effect on the lift on/ lift off productivity.